Salivary acinic cell carcinoma: reappraisal and update - Vander Poorten, V; Triantafyllou, A; Thompson, L D R; Bishop, J; Hauben, E; Hunt, J; Skalova, A; Stenman, G; Takes, R P; Gnepp, D R; Hellquist, H; Wenig, B; et al. (European archives of oto-rhino-laryngology, 2016)
Epidemiologic and clinicopathologic features, therapeutic strategies, and prognosis for acinic cell carcinoma of the major and minor salivary glands are critically reviewed. We explore histopathologic, histochemical, electron microscopic and immunohistochemical aspects and discuss histologic grading, histogenesis, animal models, and genetic events. In the context of possible diagnostic difficulties, the relationship to mammary analog secretory carcinoma is probed and a classification is suggested. Areas of controversy or uncertainty, which may benefit from further investigations, are also highlighted.
Keywords: modely nemocí na zvířatech; nádory slinných žláz; Pathology; Salivary Glands, Minor; parotis; prognóza; Mammary analog secretory carcinoma; Diagnosis, Differential; malé slinné žlázy; elektronová mikroskopie; Salivary glands; předoperační péče; Animals; Salivary Gland Neoplasms; lidé; Therapy; Humans; zvířata; Microscopy, Electron; diferenciální diagnóza; acinární karcinom; Disease Models, Animal; Carcinoma, Acinar Cell; Acinic cell carcinoma; Prognosis; Parotid Gland; Preoperative Care